Hitting the saturation point: unpacking the politics of bureaucratic reforms in hybrid regimes. Issue 4 (7th June 2017) - Bolkvadze, Ketevan
ABSTRACT: How do the survival incentives facing incumbents in hybrid regimes affect the engineering of bureaucratic reforms? This article tackles this question by departing from the literature on competitive authoritarianism and with the help of detailed empirical evidence from Georgia's public administration reforms (2004–2012). It first argues that in order to preserve their hold on power, dominant parties have to tilt the political playing field, while still upholding popular support. I posit that this dual incentive structure leads the incumbents to promote efficiency of public service, but to also curb these policies at a point that would jeopardize their ability to use administrative resources for partisan ends. Consequently, bureaucratic reforms reach a saturation point, beyond which no more reforms can be endured.